Fungal-derived cues promote ocular autoimmunity through a Dectin-2/Card9-mediated mechanism. (30th August 2017) - Brown, B R; Lee, E J; Snow, P E; Vance, E E; Iwakura, Y; Ohno, N; Miura, N; Lin, X; Brown, G D; Wells, C A; Smith, J R; Caspi, R R; et al.
Summary: Uveitis (intraocular inflammation) is a leading cause of loss of vision. Although its aetiology is largely speculative, it is thought to arise from complex genetic–environmental interactions that break immune tolerance to generate eye-specific autoreactive T cells. Experimental autoimmune uveitis (EAU), induced by immunization with the ocular antigen, interphotoreceptor retinoid binding protein (IRBP), in combination with mycobacteria-containing complete Freund's adjuvant (CFA), has many clinical and histopathological features of human posterior uveitis. Studies in EAU have focused on defining pathogenic CD4 + T cell effector responses, such as those of T helper type 17 (Th17) cells, but the innate receptor pathways precipitating development of autoreactive, eye-specific T cells remain poorly defined. In this study, we found that fungal-derived antigens possess autoimmune uveitis-promoting function akin to CFA in conventional EAU. The capacity of commensal fungi such as Candida albicans or Saccharomyces cerevisae to promote IRBP-triggered EAU was mediated by Card9. Because Card9 is an essential signalling molecule of a subgroup of C-type lectin receptors (CLRs) important in host defence, we evaluated further the proximal Card9-activating CLRs. Using single receptor-deficient mice we identified Dectin-2, but not Mincle or Dectin-1, as a predominant mediator of fungal-promoted uveitis. Conversely, Dectin-2 activation by α-mannan reproduced the uveitic phenotype of EAU sufficiently, in a process mediated by the Card9-coupled signalling axis and interleukin (IL)-17 production. Taken together, this report relates the potential of the Dectin-2/Card9-coupled pathway in ocular autoimmunity. Not only does it contribute to understanding of how innate immune receptors orchestrate T cell-mediated autoimmunity, it also reveals a previously unappreciated ability of fungal-derived signals to promote autoimmunity. Graphical Abstract: